Promoting Chair Succession through Development, Empowerment, and Encouragement - Christopher Benedetti (Academic Chairpersons Conference Proceedings, 2017)
To ensure the stability of the department, department chairs should prioritize the identification and formation of potential successors. For this interactive session, a model and related strategies, supported by real examples, will be discussed for developing, empowering, and encouraging faculty to become ready to assume the role of department chair.
Keywords: Leadership Development; Faculty; Mentoring; Succession; Department Culture